Fabrication of porous geopolymers utilizing aluminum wastes as foaming agent - CHOKKHA, Siriwan; AYAWANNA, Jiratchaya; POOWANCUM, Anurat; SINGLAEM, Thanasak; MITSOMWANG, Pusit (Journal of Metals, Materials and Minerals, 2024)
Porous geopolymers (PG) are attractive due to their simple fabrication and diverse applications. This work presents a method for fabricating PG by using aluminum salt slag (ASS) as a foaming agent and metakaolin (MK) as the precursor. Sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) are used as alkali activator solutions. The results show that the PG is fabricated by using the sequence mixing method. ASS was milled to a size of 4 µm, then mixed with an NaOH solution for 30 min. After that, MK and Na2SiO3 solution were added. The weight ratio of Na2SiO3/NaOH and solid/liquid was 2.0 and 0.6, respectively. The 7-day cured PG with 5 wt% ASS achieves a strength of 15 MPa, which is close to the minimum requirement of Portland cement of 19 MPa. PG strength decreases, while setting time and pore size increase with increasing ASS content. The knowledge of this work enables the utilization of ASS as a valuable geopolymer foaming agent.